Analysis of mortality during the winter seasons in Mexico from 2000 to 2012 - González Santiago, Omar; Balderas Rentería, Isaías; Ramírez Lara, Evangelina; Gracia Vásquez, Sandra Leticia (UANL. Facultad de Medicina, 2014)
To analyze mortality from all causes in Mexico during the winter months. Methods: Data was extracted and tabulated on monthly all-cause mortality in the general population from 2000 to 2012 from the INEGI database. Coeficients of seasonal variation in mortality were calculated. Results: In Mexico there was an increase of 14 % in mortality in the general population during winter. The more susceptible age groups were older people and children, with increases of 18% and 13% respectively. The months with low levels of mortality were April, October and September for children, adolescents and older people respectively. Conclusions: Important increases in winter mortality occur in Mexico.